Study of thermal degradation products of poly [2-(3-Mesityl-3- methylcyclobutyl)-2-ketoethylmethacrylate] - Ilter, Zülfiye; Kaya, Ismet; Erol, Ibrahim; Yildiz, H.Ibrahim; Ahmedzade, Misir (My University, 2007)
The thermal degradation of poly [2-(3-mesityl-3-methylcyclobutyl)-2- ketoethylmethacrylate] (PMKEMA) has been studied using a system consisting of a degradation tube, with a condenser for product collection, a gas-phase Infrared (IR) cell and a rotary pump. The investigation of the nature of the evolved products has been supplemented by studies of structural changes in the degrading polymer by Fourier Transform Infrared (FT-IR) technique. Changes have been investigated under programmed heating at 10°C/min from room temperature to 500°C. The product identification investigations were done by using FT-IR, 1H and 13C-Nuclear Magnetic Resonance (1H- 13C-NMR) and Gas Chromatography-Mass Spectrometer (GC-MS) techniques. The depolymerization of the main reaction is essential in thermal degradation of the PMKEMA. The degradation produces anhydride ring structures in the chain at temperatures up to about 300°C. The cleaving of ketone, aldehyde, and mesitylene compounds from side chains of the polymers is a common reaction for the polymers. A mechanism of degradation showing the formation of some of these products is discussed.
Keywords: GC-MS; Poly [2-(3-mesityl-3-methylcyclobutyl)-2-ketoethylmethacrylate]; Thermal degradation